견과류로부터 효율적인 DNA 추출 방법 비교 - 서승만(Seung-Man Suh); 박샛별(Saet-Byul Park); 김미주(Mi-Ju Kim); 김해영(Hae-Yeong Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
This study aimed to explore efficient DNA extraction methods using tree nuts. Four different DNA extraction procedures, including silica membrane method, modified silica method, cetyltrimethylammonium bromide (CTAB) method, and modified CTAB method were examined for their relative efficiency in extracting DNA from pistachio, pine nut, almond, hazelnut, cashew nut, walnut, and peanut. The quality and quantity of the extracted DNA were subsequently assessed by spectrometric measurements, gel electrophoresis, and PCR amplifications. CTAB method was the most appropriate one for extracting DNA from pine nut, cashew nut, pistachio, and peanut. However, it could be replaced by the silica membrane method for walnut and modified CTAB method for almond and hazelnut.